All-Electric Cargo Ships Data Analysis and Efficiency vs Fuel Ships Comparison - Glib Ivanov (Institut Teknologi Sepuluh Nopember, 2022)
This paper scrutinizes the common belief that electric vessels are economically unadvantageous. To achieve this, data of most known all-electric cargo ships (available in the internet as of 2021) was gathered and missing information was estimated with due diligence, to put together a sample selection. Sample vessels’ parameters including principal dimensions, speed and battery capacity were used to calculate their relative cargo transport efficiency. Different routes and speeds were used, as electric ships efficiency was compared to that of fuel-powered vessels. Electric ships were shown to be about 50% more profitable on short routes and equally as profitable on medium routes (if they were slow steaming), reasons being reduced crew, lower maintenance requirements and higher propulsion efficiency. However, at long routes and/or high speeds oil-powered ships currently dominate because otherwise a big part of cargo space would be allocated to transporting batteries, whose energy density is much lower than fuel among other reasons. This paper derives Electric ships design guidelines and helps make an informed decision on whether to use an electric propulsion ship on a given route.